2000
DOI: 10.1037/0022-3514.78.6.1109
|View full text |Cite
|
Sign up to set email alerts
|

Taxometric analyses of sexual orientation and gender identity.

Abstract: Taxa are nonarbitrary classes whose existence is an empirical question and not a matter of mere semantic convenience. Taxometric procedures detect whether numerical relations between purported indicators of conjectured taxa bear the hallmarks of true taxa. On the basis of theoretical considerations, the current study tested whether taxa underlie sexual orientation and related measures of gender identity. Two taxometric procedures, maximum covariance, making hits maximum (MAXCOV) and mean above minus below a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 47 publications
1
33
0
2
Order By: Relevance
“…from exclusive attraction to the opposite sex (heterosexuality; Kinsey score 0), through degrees of attraction to both sexes (bisexuality; Kinsey scores 1-5), to exclusive attraction to the same sex (homosexuality; Kinsey score 6). Underlying this spectrum of sexual orientation, though, there appears to be a dichotomous factor with exclusive heterosexuals in one group and those with at least some homosexual tendencies in the other-a taxonometric analysis of our data suggested that up to 15% of men and 10% of women belong to the taxon associated with homosexuality (Gangestad, Bailey, & Martin, 2000). Note that we used sexual attraction as the indicator rather than sexual behavior or sexual identity, because we believe that attraction is less affected by mate availability and social/cultural constraints and is, in this sense, more fundamental (Sell et al, 1995).…”
Section: Sexual Orientationmentioning
confidence: 74%
“…from exclusive attraction to the opposite sex (heterosexuality; Kinsey score 0), through degrees of attraction to both sexes (bisexuality; Kinsey scores 1-5), to exclusive attraction to the same sex (homosexuality; Kinsey score 6). Underlying this spectrum of sexual orientation, though, there appears to be a dichotomous factor with exclusive heterosexuals in one group and those with at least some homosexual tendencies in the other-a taxonometric analysis of our data suggested that up to 15% of men and 10% of women belong to the taxon associated with homosexuality (Gangestad, Bailey, & Martin, 2000). Note that we used sexual attraction as the indicator rather than sexual behavior or sexual identity, because we believe that attraction is less affected by mate availability and social/cultural constraints and is, in this sense, more fundamental (Sell et al, 1995).…”
Section: Sexual Orientationmentioning
confidence: 74%
“…Sexual orientation also appears mostly bimodal in its distribution and homosexuality is not simply the extreme end of a normal distribution of trait sexual orientation (even in females to an extent), another observation that works against a multifactorial model. This has led some to propose that only a very limitednumber ofdevelopmentalfactors could cause variations in sexual orientation although this explanation is also unsatisfying without proposing some theoretical tools for narrowing down putative factors (Gangestad, Bailey, & Martin, 2000;Rahman, 2005;Waddington, 1942). In contrast, the persistence Arch Sex Behav of modestly heritable sexual orientation, in the face of selection pressures against a trait that reduces reproductive fitness, argues against single factors (e.g., genes) of large effect.…”
Section: Discussionmentioning
confidence: 91%
“…Multifactorial systems can generate nonnormal data due to either measurement biases (Grayson, 1987) or to nonlinear effects of genes and environments. The debate whether sexual orientation is dimensional or categorical (Gangestad, Bailey, & Martin, 1998;Haslam, 1997) is, for this reason, not especially germane to the validity of the multifactorial assumption. The multifactorial assumption can be falsified only by discovery of a gene or environment that is sufficiently large in effect to bias parameter estimates unduly.…”
Section: Data Analysis: Genetic and Environmental Model Fittingmentioning
confidence: 99%